Anti-piracy law in Malaysian music industry: its enforcement and weaknesses / Mohd Haziq Dhiyauddin Razali and Hamidi Mohd Noh. - Razali, Mohd Haziq Dhiyauddin; Mohd Noh, Hamidi
The problem of piracy is one of the many major issues that our country has to address properly. Piracy is against the law, but nowadays in recent practice it seems more like a norm to the people to buy pirated materials. Several problems have been associated with piracy for example gangsterism, social problems, and copyright infringement is just to name a few. However, the action taken by the ministry is always criticised as not sufficient and tainted with corruption and what not. NGO's and other organization keep pressuring the ministry to provide them with a safe market without piracy and pirated material. Nevertheless, the problem still exists while the enforcers and effected parties continues arguing and pointing finger. The question is how should we address the matter and enforce the law to curb this problem and maintain the piracy rate to zero percent.